Trinexapac‐ethyl rate and timing impact on malt barley production in Virginia. Issue 2 (25th June 2021) - Swoish, Michael; Da Cunha Leme Filho, Jose Franco; Reiter, Mark; Stewart, Ryan; Thomason, Wade
Abstract: Increased demand for local malting barley ( Hordeum vulgare L.) for breweries and distilleries creates an opportunity for Virginia farmers. Lodging may decrease grain yield, reduce quality, and cause harvesting difficulties. Trinexapac‐ethyl (TE) is a plant growth regulator that reduces cell elongation and creates a shorter, sturdier stem. Field studies were initiated in 2017 and 2018 to test TE effects on 'Flavia' and 'Violetta' two‐rowed winter barleys at Blackstone and Holland, VA. Treatments consisted of: no TE; 7.2 fl oz TE acre −1 and 14.4 fl oz TE acre −1 at Zadoks growth stage (GS) 29; 7.2 fl oz TE acre −1 and 14.4 fl oz TE acre −1 at GS32; and 14.4 fl oz TE acre −1 equally split between GS29 and GS32 in a randomized complete block with four replications. Plant height, lodging incidence, and grain yield were measured. The effect of TE rate and timing varied, but all applications at GS32 resulted in significantly shorter plants. Plant lodging was decreased in 2019 at Blackstone by all TE applications compared to untreated. Plant height was decreased by as much as 42% in 2019 and plant injury was observed. Grain yield was decreased by all TE applications in Blackstone and GS32 and split applications in Holland in 2019, presumably due to stress preceding and following TE application. Plant growth at the time of application, forecasted weather, and cultivar susceptibility to lodging should all be considered when determining the optimal TE application rate and timing to reduce plant height without negatively impacting grain yield. Core Ideas: The plant growth regulator trinexapac‐ethyl decreased malt barley height which might lead to reduced plant lodging. Trinexapac‐ethyl application can potentially cause plant injury under adverse environmental conditions. Plant growth, weather, and cultivar should be considered when determining the optimal trinexapac‐ethyl application rate and timing.